Cord blood platelet gel for the treatment of inherited epidermolysis bullosa. Issue 3 (June 2018) - Gelmetti, Alessandra; Greppi, Noemi; Guez, Sophie; Grassi, Francesca; Rebulla, Paolo; Tadini, Gianluca
Abstract: The management of patients affected by epidemolysis bullosa requires an integrated approach involving different specialties. A cornerstone of clinical management is the prevention and treatment of mechanobullous ulcerations of the patient's skin, which significantly impact the quality of life and can be the cause of septic and neoplatic complications. This article describes the preliminary clinical evaluation of the use of allogeneic cord blood platelet gel, a novel blood component obtained from umbilical cord blood of healthy, term neonates, for the treatment of skin ulcers in patients with dystrophic epidermolysis bullosa. The promising clinical results obtained in this small patient group support the development of larger controlled clinical trials to compare the efficacy of platelet gel obtained from cord blood versus traditional platelet gel prepared from adult blood donors and versus current standard approaches of wound care in these patients.